2012
DOI: 10.1002/bdd.1825
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 7‐ethoxycoumarin, safrole, flavanone and hydroxyflavanone by cytochrome P450 2A6 variants

Abstract: CYP 2A6 is a human enzyme that metabolizes many xenobiotics including coumarin, indole, nicotine and carcinogenic nitrosamines. The gene for CYP2A6 is polymorphic. There are few data available to clarify the relationship between P450 genetic variants and the metabolism of materials in food. The CYP 2A6 wild-type protein and 13 mutants (CYP2A6.1, CYP2A6.2, CYP2A6.5, CYP2A6.6, CYP2A6.7, CYP2A6.8, CYP2A6.11, CYP2A6.15, CYP2A6.16, CYP2A6.17, CYP2A6.18, CYP2A6.21, CYP2A6.23 and CYP2A6.25) were co-expressed with NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…CYP2A6*7 contains a missense mutation, 6558G>A, which produces an Ile471Thr amino acid change that decreases the enzymatic activity to metabolize some substrates for in vivo and in vitro assays (Ariyoshi et al, 2001[7]; Uno et al, 2013[138]; Xu et al, 2002[147]).…”
Section: Cyp2a6 Genetic Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2A6*7 contains a missense mutation, 6558G>A, which produces an Ile471Thr amino acid change that decreases the enzymatic activity to metabolize some substrates for in vivo and in vitro assays (Ariyoshi et al, 2001[7]; Uno et al, 2013[138]; Xu et al, 2002[147]).…”
Section: Cyp2a6 Genetic Variantsmentioning
confidence: 99%
“…CYP2A6*25 is the result of several point mutations, some of them in 5'UTR: -1301A>C, -1289G>A and -745A>G, also 22C>T, 51G, 768A>T, 1620T>C, 1672T>C, 2296C>T, 2483G>A, 2605G>A, 2921G>A, 2994T>C, 4636A>C, 5668A, 6586T>C, 6692C>G and 7160A>G that result in the amino acid change of Phe118Leu (Mwenifumbo et al, 2008[87]), it has been shown that its enzymatic activity is decreased in some substrates (Ho et al, 2009[49]; Mwenifumbo et al, 2008[87]; Uno et al, 2013[138]).…”
Section: Cyp2a6 Genetic Variantsmentioning
confidence: 99%
“…In addition, two expression vectors, CYP2A6.1 and CYP2A6.25 were obtained as described previously [20]. In addition, two expression vectors, CYP2A6.1 and CYP2A6.25 were obtained as described previously [20].…”
Section: Expression Of Cyp2a6 Variants In E Colimentioning
confidence: 99%
“…Many CYP2A6 genetic variants, which showed reduced enzymatic activity, are associated with slower metabolism of nicotine and cotinine [12][13][14][15]. In a previous study, it was found that CYP2A6.25, which comprises an amino acid substitution of F118L, shows a decrease in coumarin 7hydroxylation and safrole hydroxylation [20]. There are few reports clarifying the contributions of the specific amino acid residues that are mutated in these CYP2A6 variants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation